Data‐derived optimization of sensitivity requirements for upcoming auroral imaging missions. Issue 9 (18th September 2017) - Donovan, Eric; Uritsky, Vadim M.; Unick, Craig; Troyan, Vladimir
Abstract: Using an extensive database of ultraviolet images of the nighttime sector of the northern auroral oval obtained from the POLAR spacecraft and data analysis tools adopted from statistical mechanics of turbulent flows, we identify scaling relations describing substorm time variability of the auroral intensity as a function of spatial scale and auroral intensity level. By extrapolating these relations to scales smaller than those resolved by previously flown auroral missions, we derive contrast and sensitivity constraints for a next‐generation global auroral imager. The outcomes of this analysis, combined with the results reported by Uritsky et al. (2010), make it possible to optimize sensitivity and resolution requirements for future auroral imaging missions intended to observe auroral structure and dynamics across wide ranges of spatial and temporal scales. Key Points: Data‐derived requirements for next‐generation UV auroral imaging missions Statistical features of UV auroral emission events New technique for analyzing collective behavior of auroral precipitation events